The role of the microbiome in allergic dermatitis-related otitis externa: a multi-species comparative review - Houtsaeger, Cyrelle; Pasmans, Frank; Claes, Ingmar; Vandenabeele, Sophie; Haesebrouck, Freddy; Lebeer, Sarah; Boyen, Filip (Frontiers in Veterinary Science, 2024)
The external ear canal, characterized by species-specific structural and physiological differences, maintains a hostile environment that prevents microbial overgrowth and foreign body entry, supported by factors such as temperature, pH, humidity, and cerumen with antimicrobial properties. This review combines several studies on the healthy ear canal’s structure and physiology with a critical approach to the potential existence of an ear microbiome. We use a comparative multi-species approach to explore how allergic conditions alter the ear canal microenvironment and cerumen in different mammalian species, promoting pathogen colonization. We propose a pathogenetic model in which allergic conditions disrupt the antimicrobial environment of the EEC, creating circumstances favorable for facultative pathogenic micro-organisms like Staphylococcus and Malassezia species, leading to otitis externa (OE). A better understanding of the underpinning mechanisms may lead to innovative approaches to disease mitigation.